Assessing the performance of Alphitobius piceus (Oliver, 1792) as novel feeder insect species for small sized postmetamorphic frogs - Octavian CRAIOVEANU; Cristina CRAIOVEANU; Mihai-Iacob BENȚEA; Cristian-Ovidiu COROIAN; Vioara MIREȘAN (Studia Universitatis Babeș-Bolyai. Biologia)
One of the major difficulties of frog farming is providing adequate food in the first few weeks after the metamorphosis. This is a critical time frame, with rapid growth and high mortality. The established feeder insect species used throughout this delicate stage (cricket and mealworm larvae, adult fruit flies) are suitable from a trophic perspective, but present challenges and difficulties that influence the production costs. The aim of this study is to assess the performance of an alternative feeder species – Alphitobius piceus – with a simpler production technology and a lower production cost. Two species of feeder insect were used: the conventionally used Acheta domestica larvae as control species, and Alphitobius piceus larvae as experimental species. As model anuran we used the European common frog, Rana temporaria. The experimental insect species was easily accepted and produced a strong feeding response in the post-metamophic frogs. There were no significant differences between the control and experimental groups in terms of body condition index and mortality, however survival was better in the experimental group. This similarity indicates a high potential of Alphitobius piceus as feeder species for the newly metamorphosed frogs and also a good economic opportunity for frog farms.